Growth and characterization of urea-doped KDP crystals - Pritula, I.; Kosinova, A.; Kolybayeva, M.; Puziko, V.; Bondarenko, S.; Tkachenko, V.; Tsurikov, V.; Fesenko, O. (Functional Materials, 2007)
Potassium dihydrophosphate single crystals were grown from aqueous solutions onto a point seed using temperature reduction method by doping with different molar values of Urea. The characterization of the grown crystals was made by visible and fourier transform infrared spectroscopy, Vicker's hardness studies, X-ray powder diffraction, nonlinear optical and laser damage threshold measurements. By comparing these crystals with the ones grown from the pure solution, it is shown that 0.2/2.0 M of the Urea additive enhances the laser damage threshold and the second harmonic efficiency more than by 25 and 20 %, respectively. The Vicker's hardness studies carried out on (100) and (001) crystallographic planes show an increased hardness of the doped crystals (grown in the presence of Urea additive) on the plane (001) in comparison with that of pure potassium dihydrophosphate crystal.